POTÊNCIA ALELOPÁTICO DA BRACHIARIA RUZIZIENSIS SOBRE O DESENVOLVIMENTO DA AVEIA E DO TRIGO - FARIA JUNIOR, Jairo Borges (2019)
Vegetation covering is used to provide organic matter to the soil, improve soil, chemical and physical characteristics, as well as help to control erosion, reducing organic fertilizer costs and environmental impacts. Wheat (Triticum aestivum) and Oats (Avena sativa) are important agricultural crops for the Brazilian economy and Brachiaria ruziziensis is a forage widely used in succession with these crops and as vegetation covering. This grass has stood out due to high field stabilization and growth throughout the year. Studies indicate their allelopathic potential on invasive plants and crops of interest. Therefore, this work aimed to evaluate the allelopathic effect, in laboratory and in pots, of Brachiaria ruziziensis on wheat and oat germination and development. The laboratory experiments were carried out at the University Center of Maringá - Unicesumar, in a B.O.D. incubator chamber, 25ºC with a photoperiod of 12 hours, for seven days. The treatments consisted of different concentrations of Brachiaria ruziziensis aqueous extract (0, 25, 50, 75 and 100%). Pot experiments were installed at UNICESUMAR / Biotec experimental farm in the presence or absence of 3.5% brachiaria cover. The experimental design was completely randomized with five replications, and the results were evaluated by analysis of variance and the means between treatments compared by the Scott Knott test at 5% significance.